Greening of potato tubers after harvest: effect of planting date and cultivar (Research, Society and Development, 2020)
The different potato planting dates in southern Brazil have different climatic factors that affect the yield and quality of the tubers produced. The objective of this work was to test the effect of planting date and potato cultivars on the postharvest greening of tubers. The treatments consisted of three planting dates (October, December, and February) and three potato cultivars (Agata, BRS Clara, and BRS F63 Camila). It was observed that the tubers harvested in February were less susceptible to greening, probably due to the higher physiological maturity of the tubers produced in this planting date. Tubers of cv. BRS Clara had lower greening than the tubers of the other cultivars. In addition to the light conditions, the cultivar and storage air temperature are also important factors that affect greening rates. Care must be taken with these factors to avoid losses of tubers by greening.